Influence of Channel Silicon Thickness and Biological Material Permittivity on nTFET Biosensor - Macambira, Christian N.; Agopian, Paula G. D. [UNESP]; Martino, Joao A.; IEEE (Ieee, 2018)
This work analyzes the effect of channel silicon thickness for different biological materials on n-type Tunnel-FET (nTFET) working as a biosensor. The bioelement materials are simulated using different dielectric permittivity materials (c) localized at the drain underlap region. The results of this work show that using the ambipolar current of the Tunnel-FET it presents better sensitivity. The best results for TFETs biosensor were obtained for the drain underlap of 15 nm and channel silicon thickness of 5 nm.
Keywords: Biosensor; TFET; Silicon Thickness; Underlap; Sensitivity; Permittivity